Application of Polyphosphoric Acid‐Mediated Acyl Migration for Regiospecific Synthesis of Diverse 2‐Acylpyrroles from Chalcones. (27th February 2019) - Kumar, Togiti Uday; Thigulla, Yadagiri; Rangan, Krishnan; Bhattacharya, Anupam
Abstract : A metal‐free approach for the synthesis of 2‐acylpyrroles is reported in this paper. Synthesis of the target molecule started from chalcones and was carried out in two steps. Initial step involved the conversion of chalcones to corresponding 4‐substituted‐3‐acylpyrroles by reaction with TosMIC. In the subsequent step, target molecules were obtained in modest to good yields by polyphosphoric acid‐mediated acyl rearrangement of 3‐acylpyrroles to their 2‐acyl congeners. The crucial final step was amenable to diverse substitutions on pyrrole ring. Preliminary experiment for the determination of mechanism indicated the involvement of acylium ion. Abstract :